PERAN SANTRI DALAM MEMPERKUAT SEMANGAT KEBANGSAAN - Zulfikar, Zulfikar; Hadi, Agustinus Sutriyanto; Sukoco, Sukoco (Journal of Democratia; Vol 2 No 02 (2024): Jurnal Democratia Pendidikan Pancasila dan Kewarganegaraan, 2024)
There are some groups that accuse Islam of violence so that people think in the name of religion that this is synonymous with the teachings of Islamic boarding schools, from here the author straightens out the notion that students have always played a part in fighting for the Unitary State of the Republic of Indonesia.       This study aims to explain the role of the santri in strengthening the spirit of nationalism in SMP IT ADA KAB.MAGELANG students  and to describe and analyze the role of the students in strengthening the national spirit in Islamic boarding schools at SMP IT MAGELANG . This study uses a qualitative descriptive method. Techniques used for data collection; structured interviews, observation, and documentation as well as test the credibility using triangulation.          Based on the results of the research, it is known that the role of Santri in cultivating the national spirit is to play a role in fostering the determination to live a free, independent and united national life by providing experience through ustadz/ustadzah as an example to be imitated by the santri. Playing a role in fostering a sense of love for the homeland and nation with a reciprocal relationship between the ustadz and the students. Playing a role in fostering democratic attitudes by instilling democratic values ??in the learning process, and playing a role in fostering social solidarity with students by directing students in community activities.